Evaluation of Land Suitability for Oil Palm Based on Geographic Information System in Konawe Selatan District - Aldiansyah, Septianto; Saudi, Fitriyani; Ati, Amniar (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2026)
Oil palm is an important commodity in the industrial sector. Konawe Selatan Regency has begun to develop oil palm plantations in various regions, but land suitability analysis with a spatial approach has never been carried out. This study is important to support oil palm cultivation by taking into account environmental characteristics. This study utilizes Geographic Information Systems using parameters of temperature, rainfall, dry month, soil texture, soil depth, soil pH, slope, and erosion. Konawe Selatan Regency has oil palm suitability that is classified as very suitable (S1) 0.04%, quite suitable (S2) 40.41%, marginally suitable (S3) 31.19%, and not suitable (N) 28.36%. The limiting factors in this area are hotter and colder temperatures and steep slopes. Oil palm development must be carried out with primary consideration in conservation areas, considering that Konawe Selatan Regency has agronomic and ecological limitations.